2015
DOI: 10.17577/ijertv4is031027
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Carbon Dioxide Laser on Polymers

Abstract: This paper presents an overview of laser machining process and investigates CO2 laser cutting on polymers with various thickness. Laser Beam Machining is mainly used in many manufacturing industries. The highly collimated beam of a laser can be further focused to a microscope dot of extremely high energy density for cutting. Polymers are commonly used in automobile industries, medical, biotech devices, in the microelectronic and sensor industries for insulating layers in multi-level devices. Laser beam cutting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…CO 2 laser cutting is an established material manufacturing technology, widely used due to its low cost and rapidity and good quality depending on the material. This technique has been applied to both metallic and nonmetallic materials, for example, glass, wood, thermoplastics, thermosets, and elastomers. During cutting, the laser beam is focused onto the material surface, causing a localized melting or vaporization or both . The heat generated by the laser diffuses through the material altering its microstructure and properties in an area named the heat affected zone (HAZ) (Figure A-i).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CO 2 laser cutting is an established material manufacturing technology, widely used due to its low cost and rapidity and good quality depending on the material. This technique has been applied to both metallic and nonmetallic materials, for example, glass, wood, thermoplastics, thermosets, and elastomers. During cutting, the laser beam is focused onto the material surface, causing a localized melting or vaporization or both . The heat generated by the laser diffuses through the material altering its microstructure and properties in an area named the heat affected zone (HAZ) (Figure A-i).…”
Section: Resultsmentioning
confidence: 99%
“…Leaching of polymeric components from the bulk material is another issue in microfluidic systems. Although the mobility of low molecular weight oligomers in the whole polymer is known, few studies have looked into this potential problem in detail . It has been suggested that this uncontrolled and undesired leaching could lead to cytotoxicity, interference with cellular signaling pathways, or PCR inhibition .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a wavelength of 10,600 nm and unprofessional usage can result in poor dimensional accuracy of engraved structures. According to the research [51,52] controlling the speed of engraving and laser power are the two key factors for controlling the quality of engraved elements.…”
Section: Width Of the Engraved Lines On The Printing Platesmentioning
confidence: 99%
“…1,2 The cutting is achieved by focusing the laser beam on the surface of the material which results in local heating, melting, and vaporization. 3 The mode of machining of polymers depends on the material’s behavior during laser interaction. Generally, thermoplastic machining is carried out by fusion mechanism while the cutting of Polymethylmethacrylate (PMMA) is achieved by vaporization.…”
Section: Introductionmentioning
confidence: 99%